Medicinal Plants on Acne inducing Bacteria - Tanushree Tulsian Samanta,; Ankita Das, (International Journal of Phytomedicine, 2015)
Acne is a cutaneous pleomorphic disorder of the pilosebaceous unit involving abnormalities in sebum production and is characterized by both inflammatory (papules, pustules and nodules) and non-inflammatory (comedons, open and closed) lesions. Propionibacterium acnes and Staphylococcus epidermidis are common pus-forming microbes responsible for the development of various forms of Acne vulgaris. The present study was conducted to evaluate antimicrobial activities of seven medicinal plants against acne-inducing bacteria. Acetonic and aqueous extracts of Azadirachta indica (leaves), Curcuma longa (root), Aloe vera (leaves), Withania somnifera (leaves), Terminalia arjuna (bark), Ocimim sanctum (leaves), Santalum album (wood) were tested for antimicrobial activities by agar diffusion, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) methods. The results from the agar diffusion method showed that five medicinal plants could inhibit the growth of acne-inducing bacteria. Among these Azadirachta indica, Curcuma longa and Terminalia arjuna had strong inhibitory effects. Based on MIC, the acetonic extracts of Azadirachta indica and Curcuma longa had the greatest antimicrobial effects. Taken together, the present study indicated that Azadirachta indica had a strong inhibitory effect on acne-inducing bacteria.